PERLAKUAN AKUNTANSI AKTIVA TETAP PADA PT. ARINA KARYA SENTOSA NEUSU BANDA ACEH - aliamin, aliamin (Fakultas Ekonomi Universitas Muhammadiyah Aceh, 2011)
The aim of this research was to know how the fix assets record in PT. Arina Karya Sentosa (subject of research), what is the assets recorded as of Indonesian Accounting Standard (Standar Akuntansi Keuangan/SAK). The method to use of this research was qualitative descriptive, the operating of this method are to compare both the theoretical with PT Arina Karya Sentosa recorded to fix assets, and recently the researcher make decisions and recommendation to improve the fix assets recording system. The result of this research were to find PT. Arina Karya Sentosa Banda Aceh classified fix assets to; buildings, project equipments, office equipments, vehicles. The depreciation method to measure the right value of all assets was manual method that they use to measure their assets, did not use method recommendation from Indonesian Accounting Standard. Even thought, PT. Arina Karya Sentosa was recording and prepare the fix assets as of Indonesian Financial Accounting Standard in financial report, except the depreciation method but in audit review by independent auditor these was no problem. Key words: fix assets recording, fix assets method, fix asset prepare in financial report. Carl S.Warren, James M.Reeve, Philip E.fess (2005). Pengantar Akuntasi. Edisi 21, Penerbit Salemba empat. Jakarta Drs. Djarwanto Ps. (2004) Pokok-Pokok Analisa Laporan Keuangan. Edisi Kedua, Penerbit BPFE Yogyakarta. Yogyakarta Ikatan Akuntansi Indonesia (2004). Standar Akuntansi Keuangan. Per 1 Okt 2004, Penerbit Salemba Empat. Jakarta Junaidy Slamet Setiawan (2005). Kajian Terhadap Beberapa Metode Penyusutan Dan Pengaruhnya Terhadap Perhitungan Beban Pokok Penjualan. (Http://www.petra.co.id) Muhammad Nuh (2001). Intermediate Accounting. Penerbit Mondial Musa Grafik Soemarso S.R (2004). Akuntansi Suatu Pengantar. Edisi ke-4, Penerbit Salemba Empat, Jakarta